Incidence and occupational pattern of leukaemias, lymphomas, and testicular tumours in western Ireland over an 11 year period. Issue 10 (October 1998) - Kelleher, C; Newell, J; MacDonagh-White, C; MacHale, E; Egan, E; Connolly, E; Gough, H; Delaney, B; Shryane, E
Abstract : STUDY OBJECTIVE: To determine incidence of the following malignancies, testicular tumours, all leukaemias and all lymphomas in the West of Ireland in an 11 year period. Secondly, to examine the relation between disease patterns and available occupational data in male subjects of working age. DESIGN: A census survey of all cases occurring in the three counties in the Western Health Board (WHB) area, Galway, Mayo and Roscommon, for the 11 year period 1980 to 1990 inclusive. Average annual age standardised incidence rates for the period were calculated using the 1986 census data. Rates for the area are compared with rates from the southern region of Ireland, which had a tumour registry. Trends over the time period are evaluated. All male subjects for whom occupational data were available were categorised using the Irish socioeconomic group classification and incidence rates by occupation were compared using the standardised incidence ratio method. In one of the counties, Galway, a detailed occupational history of selected cases and an age matched control group was also elicited through patients' general practitioners. SETTING: All available case records in the West of Ireland. RESULTS: There are no national incidence records for the period. Compared with data from the Southern Tumour Registry, the number of cases of women with myeloid leukaemias was significantly lower. Male leukaemia rates were significantly lower as a group (SIR 84 (95% CI 74, 95) but not when considered as individual categories. Regression analysis revealed an increasing trend in the number of new cases of non-Hodgkin's lymphoma among both men (r = 0.47, p = 0.02) and women (r = 0.90, p = 0.0001) and of chronic lymphocytic leukaemia in men (r = 0.77, p = 0.005) and women (r = 0.68 p = 0.02) in the WHB region over the last decade. Four hundred and fifty six male cases over the age of 15 years were identified and adequate occupational information was available for 74% of these. Standardised incidence ratios of testicular tumours 100, 938) and agriworkers other than farmers (SIR 377, 95% CI 103, 967). There were also significantly increased incidence ratios for both non-Hodgkin's lymphoma (SIR 169, 95% CI 124, 266) and three categories of leukaemias among farmers. Hodgkin's disease and acute myeloid leukaemias were significantly increased among semi-skilled people. Interview data with 90 cases and 54 controls of both sexes revealed that among farmers, cases (n = 31) were significantly less likely than controls (n = 20) to use tractor mounted spraying techniques (OR = 0.19 (95% CI 0.04, 0.80)) and less likely to wear protective masks (OR 0.22 (95% CI 0.05, 0.84)). CONCLUSIONS: Trends of increase in non-Hodgkin's lymphoma and some leukaemias are consistent with studies elsewhere. The study provides further evidence of the relation between agricultural work and certain lymphoproliferative cancers. The possible carcinogenic role of chemicals used in agricultural industries must be considered as an explanation.